(untitled) (Review Journal of Neurological & Medical Sciences Review, 2026)
This study focuses on the use of morin hydrate as a reducing agent and stabilizer for the green synthesis and characterization of zinc oxide (ZnO) and iron oxide (Fe3O4) nanoparticles, as well as the comparative evaluation of their therapeutic effects. The use of a naturally occurring flavonoid (morin) has demonstrated antioxidant potential, and thus was deemed appropriate for developing biocompatible nanoparticles via an environmental-friendly synthetic route. Various methods of analysis (UV-visible spectroscopy, Fourier-transform infrared spectroscopy, X-ray diffraction, dynamic light scattering, scanning electron microscopy) were employed to characterize the newly created nanoparticles according to their structural, morphological, and physicochemical characteristics. Biologically-based evaluations were made on the nanoparticles by determining their ability to exhibit antioxidant, antimicrobial, and cytotoxic activities. The results suggested that the nanoparticles formed were stable, in the nanosphere size range; they possessed a crystalline structure; and they were well-dispersed. ZnO nanoparticles demonstrated greater antimicrobial activity against certain pathogenic microorganisms than did the iron oxide nanoparticles, while the iron oxide particles exhibited better biocompatibility and a significant level of antioxidant activity compared to the ZnO nanoparticles. Cytotoxicity testing demonstrated that both sets of nanoparticles had therapeutic potential that was concentration-dependent; therefore both types of nanoparticles will likely be suitable for use in medicine. The biodistribution of the morin with the nanoparticles appears to improve the stability and biological activity through means of the synergistic nature of the morin with either zinc oxide or iron oxide. Keywords: Morin hydrate, Green synthesis, Zinc oxide nanoparticles, Iron oxide nanoparticles, Nanotechnology, Antioxidant activity, Antimicrobial activity, Cytotoxicity, Biocompatibility, Therapeutic evaluation